PROCESSING PERFORMANCE OF STEVIA (STEVIA REBAUDIANA BERTONI) BE CONSIDERED AS A CONDITION OF ALTERNATIVE CROP - García P., J. M. (2009)
A lthough stevia (Stevia rebaudiana Bertoni) is a native of Peru, has become a business opportun ity far the development of the crop due to the variety of ecologica l zones to the country. The contribution of the show lies in chemical engineering with firsthand information source for the competitive advantage that this plan! will become a new alternative crop for Peru, showing al the preliminary technical and economic feasibility of processing.